Denoising of ultrasound images affected by combined speckle and Gaussian noise. Issue 12 (8th October 2018) - Mafi, Mehdi; Tabarestani, Solale; Cabrerizo, Mercedes; Barreto, Armando; Adjouadi, Malek
Abstract : This study introduces an image denoising method in the presence of combined speckle and Gaussian noise. The dual‐tree complex wavelet transform is applied to the image in order to obtain specific coefficients characterising these types of noise. Then, these extracted coefficients are removed by thresholding and an inverse wavelet transform is applied in order to obtain the reconstructed image. A comparison between the dual‐tree and standard wavelet‐based denoising filters is provided on the basis of different structural metrics. Finally, in order to remove any remaining noise, a spatial denoising filter is applied to the image. The results obtained on medical ultrasound images corrupted by this noise combination support the authors' assertion on the method's resilience to the combined effects of speckle and Gaussian noise, and are compared to well‐known and most effective speckle–Gaussian denoising filters.